Defense reactions of Dermatobia hominis (Diptera : Cuterebridae) larval hemocytes - Faraldo, A. C.; Lello, E. (Inst Histol Embriol-conicet, 2003)
The defense reactions against biological (Histoplasma capsulatum and Escherichia coli) and non-biological materials (China ink and nylon thread) were tested in vivo in third instar larvae of Dermatobia hominis. The cellular defense performed by larval hemocytes was observed under electron microscopy. China ink particles were phagocytosed by granular cells 5 h after injection. E. coli cells were internalized by granular cells as early as 5 min after injection and totally cleared 180 min post-injection, when many hemocytes appeared disintegrated and others in process of recovering. H. capsulatum yeasts provoked, 24 h after being injected, the beginning of nodule formation. Nylon thread was encapsulated 24 h after the introduction into the hemocoel. Our results suggest that granular cells were the phagocytic cells and also the responsible for the triggering of nodule and capsule formation. In the presence of yeasts cells and nylon thread, they released their granules that chemotactically attracted the plasmatocytes that on their turn, flattened to surround and isolate the foreign material.
Keywords: Dermatobia hominis; hemocytes; phagocytosis; nodule formation; encapsulation